Ectopic Mesiodens Near the Anterior Nasal Spine and Nasopalatine Canal: A Rare Case Report - Krishnamurthy Kavitha; Dharmendra Kumar MG; Muralidharan R; Joshua Dullapalli; Shree Ram Subba Reddy (The Bioscan, 2026)
Mesiodens, a type of supernumerary tooth, are typically located in the maxillary midline, positioned between the two central incisors. Although these teeth are commonly impacted within the dental arch, cases where they erupt ectopically into unusual anatomical sites, such as the nasal cavity or adjacent to the anterior nasal spine, are exceedingly rare. This report details a unique case involving the ectopic eruption of a mesiodens located near the anterior nasal spine in a 14-year-old male patient. The mesiodens was successfully surgically removed under local anesthesia. This report discusses the patient’s clinical presentation, radiographic findings, the surgical approach employed, and the postoperative outcome, providing insights into the management of such a rare condition.